Ammonia sensor based on polypyrrole–graphene nanocomposite decorated with titania nanoparticles. Issue 5 (June 2015) - Xiang, Cuili; Jiang, Dadi; Zou, Yongjin; Chu, Hailiang; Qiu, Shujun; Zhang, Huanzhi; Xu, Fen; Sun, Lixian; Zheng, Liangjun
Abstract: A composite of polypyrrole (PPy) and graphene nanoplatelets (GNs) decorated with titanium dioxide (TiO2 ) nanoparticles (TiO2 @PPy–GN) was synthesized by a sol–gel process combined with in situ chemical polymerization. The microstructure, morphology, and crystallinity of the TiO2 @PPy–GN nanocomposite were characterized by Fourier-transform infrared spectrometry, scanning electron microscopy, transmission electron microscopy, and X-ray diffraction. The results indicate that the TiO2 nanoparticles with a diameter of 10–30 nm were well dispersed on the PPy–GN composite. The TiO2 @PPy–GN nanocomposite exhibited good electrical-resistance response to NH3 at room temperature. Compared to the PPy–GN thin film, the TiO2 @PPy–GN thin film showed enhanced NH3 -sensing properties in the form of higher sensitivity and much faster response under the same conditions. The selectivity and stability of the NH3 sensor based on theTiO2 @PPy–GN nanocomposite were also investigated.